1980
DOI: 10.1073/pnas.77.5.2711
|View full text |Cite|
|
Sign up to set email alerts
|

Ascorbic acid inhibits replication and infectivity of avian RNA tumor virus.

Abstract: Ascorbic acid, at nontoxic concentrations, causes a substantial reduction in the ability of avian tumor viruses to replicate in both primary avian tendon cells and chicken embryo fibroblasts. The virus-infected cultures appear to be less transformed in the presence of ascorbic acid by the criteria of morphology, reduced glucose uptake, and increased collagen synthesis. The vitamin does not act by altering the susceptibility of the cells to initial infection and transformation, but instead appears to interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Ascorbate also has been found to have no effect on total collagen synthesis in human synovial cells, but this may be due to the much shorter duration oftreatment used (29). In primary avian tendon cells, however, collagen synthesis was stimulated by ascorbate (15) although a later report from the same laboratory contradicted the earlier observation (30). Furthermore, it was difficult to be sure if this was a primary effect or was secondary to changes in cell density which has been found to exert a significant influence on collagen synthesis relative to noncollagen protein synthesis (17).…”
Section: Methodscontrasting
confidence: 47%
“…Ascorbate also has been found to have no effect on total collagen synthesis in human synovial cells, but this may be due to the much shorter duration oftreatment used (29). In primary avian tendon cells, however, collagen synthesis was stimulated by ascorbate (15) although a later report from the same laboratory contradicted the earlier observation (30). Furthermore, it was difficult to be sure if this was a primary effect or was secondary to changes in cell density which has been found to exert a significant influence on collagen synthesis relative to noncollagen protein synthesis (17).…”
Section: Methodscontrasting
confidence: 47%
“…In particular, Bissell et al (1980) found similar suppression of viral replication in cell culture with L-and D-ascorbic acid. Accordingly, in the current state of knowledge it seems reasonable to combine the Clegg & Macdonald (1975) L-and D-isomer groups.…”
Section: Reply By Hemilämentioning
confidence: 53%
“…The half-life of AsA in the medium is less than 8 hr (16). Therefore, AsA was added repeatedly to the culture at 12-hr intervals, and its effect on antibody production was studied (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that AA-2G stimulated PWM (17) and SAC (18)-induced antibody production remark ably, whereas AsA had no stimulating effect by a single addition. AsA in the medium rapidly decomposed with a very short half-life (1-8 hr) (16), but the high stability of AA-2G in neutral solution (6, 9) makes it more useful than AsA in a long-term cell culture. Moreover, we confirmed that AA-2G had no cytotoxicity in PBLs, but AsA showed cytotoxicity at concentrations higher than 0.25 mM.…”
Section: Discussionmentioning
confidence: 99%